¿Religiones del amor? Reflexiones sobre religión y violencia en las grandes religiones monoteístas - Uhde, Bernhard (2005)
The great monotheistic religions -Judaism, Christianity, and Islam- agree in announcing God’s love for men, while demanding men’s love for God and for their neighbors. However, a brief look at these religions’ praxis leads to doubt whether this love is not a mere statement, while in history and at present were and are still imposed exclusive truth claims exercising violence against the adepts of the own religion ("internally”) and, in especial, against the followers of other religions ("externally”) in order to attain political power. Now, a distinction between the just sovereign power of God and detrimental violence should be made, asides from the fact that God’s sovereign power and God’s concept is not the same in the three great monotheistic religions. In Judaism God governs with love and as king, in Christianity with love and as servant, in Islam with love and majesty. Nevertheless, sovereign power is exclusive of God and detrimental violence is never desired among men. Only thus is power constitutive of religion’s inner nature, but not of the relation between religions or of religions with the world: "There is no coercion in religion".